Examining hedonic and eudaimonic well-being in emerging adults from Hong Kong: Does amor Fati account for well-being beyond the role of affectivity? - Stephen Cheong Yu Chan; Qi Lu Huang; Edward C. Chang (Acta Psychologica)
This study examines the significance and utility of amor fati—an existential construct reflecting complete life affirmation—as a positive psychological variable in predicting both hedonic and eudaimonic well-being among emerging adults in Hong Kong. Analyzing 303 permanent residents aged 18 to 29 years, we investigated if amor fati adds to the prediction of subjective happiness (hedonic well-being) and flourishing (eudaimonic well-being) beyond affectivity. Hierarchical regression analyses revealed that affectivity accounted for a significant portion of the variance in both well-being indices. Importantly, after controlling for positive and negative affectivity, amor fati emerged as a significant independent predictor, underscoring its construct validity and unique contribution to accounting for well-being. These findings have implications for positive psychology theory and practice, particularly in non-Western contexts, and suggest that interventions aimed at cultivating and embracing an attitude toward one's fate may promote optimal well-being in emerging adults from Hong Kong.